2014
DOI: 10.1302/0301-620x.96b9.31831
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement through a posterior approach using a 22 mm diameter femoral head

Abstract: Despite a lack of long-term follow-up, there is an increasing trend towards using femoral heads of large diameter in total hip replacement (THR), partly because of the perceived advantage of lower rates of dislocation. However, increasing the size of the femoral head is not the only way to reduce the rate of dislocation; optimal alignment of the components and repair of the posterior capsule could achieve a similar effect. In this prospective study of 512 cemented unilateral THRs (Male:Female 230:282) performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…13 causes for dislocation, regardless of the idoneity of the cup position, a finding also reported by others [7,24,32]. We also observed that the lever arm distance and the height of the greater trochanter differed among the different designs, which may also affect the differences observed in the rates of dislocation.…”
Section: Accepted Manuscriptsupporting
confidence: 86%
See 1 more Smart Citation
“…13 causes for dislocation, regardless of the idoneity of the cup position, a finding also reported by others [7,24,32]. We also observed that the lever arm distance and the height of the greater trochanter differed among the different designs, which may also affect the differences observed in the rates of dislocation.…”
Section: Accepted Manuscriptsupporting
confidence: 86%
“…THA, with a 22.225 mm diameter femoral head operated through a posterior approach with a capsule repair, was associated with a low rate of dislocation [24]. They do not support the idea of using large-diameter heads since data from Registries and wear problems are being reported.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Blumenfeld and Bargar hypothesized that increasing the femoral head diameter and revising the liner of a recurrently dislocating THR will not always be successful [24]. Therefore, a larger femoral head does not ensure stability and increasing the size of the femoral head is not the only way to reduce the rate of dislocation; optimal alignment of the components and repair of the posterior capsule could achieve a similar effect [25].…”
Section: Discussionmentioning
confidence: 99%
“…Certain centers are still using a 22-mm head with a high success and low dislocation rate in primary hip replacement [25,29] and for example, the Norwegian Arthroplasty Register showed a higher number of hip replacements with a 22-mm head than any other head size [30]. Also, Dutch Arthroplasty Register showed that femoral head sizes of 22 to 28 mm and 32 mm had a comparable risk of revision for any reason except dislocation, while 36-mm femoral head THAs had a 16% increased risk [31].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PA has generally been associated with higher dislocation rates of 1.7%–5.3% 404142. Although recent literature has demonstrated improved stability with posterior capsular repairs 42434445. Randomized prospective data on dislocations is lacking, but several meta analyses and large retrospective comparative studies have demonstrated stability superiority with the anterior based approaches versus PA 344647484950.…”
Section: Discussionmentioning
confidence: 99%